Grassroots participation and agency in bilingual education processes in Mozambique - Chimbutane, Feliciano (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The intention of this introduction to this special issue is to give the context within which the three articles in the issue were born and foreground the main themes emerging from the discussions offered in each of them.